Novel fondaparinux protocol for anticoagulation therapy in adults with renal failure and suspected heparin-induced thrombocytopenia: a retrospective review of institutional protocol - Dania Ghaziri; Hassan Dehaini; Mayyas Msheik; Marwan Bahmad; Maya Zorkot; George Abi Saad (BMC, 2023)
Plain Language Summary New Fondaparinux Protocol to Reduce the Risk of Blood Thickening and Blood Clots Formation in Adults with Kidney Disease and Heparin-induced Thrombocytopenia (drop in platelets after the use of heparin): A Test Study. Fondaparinux is a drug used to treat patients suffering from thrombosis (clot in blood) and prevent vessels occlusions. When patients have kidney disease, the ideal treatment for thrombosis would be heparin; and, in case of Heparin Induced Thrombocytopenia (HIT), an unexpected drop in platelets after the use of heparin, the ideal treatment would be argatroban or bivalirudin. Fondaparinux can be used for HIT. However, studies recommend against its use in kidney disease as it might accumulate and cause bleeding. We were put in a challenging situation where we had patients with life-threatening thrombosis, kidney disease, HIT and unavailability of both argatroban and bivalirudin. Our only option was fondaparinux. We had to devise a safe and efficient protocol. The starting dose was the one used had the patient had a normal kidney function. Then, anti-Factor Xa activity was regularly measured with the target level 0.6-1.3units/ml 4 h after a dose. The dose was individualized, changed based on the Factor Xa activity result, the risk of bleeding or thrombosis, the overall kidney function and the need for dialysis. Our protocol was tested on 10 patients. All our patients could reach the target and safe Factor Xa activity. We had 2 exceptions. The first had a clotting event despite having therapeutic Factor Xa activity and the second was a very sick cancer patient who was bleeding despite skipping many doses of fondaparinux. We consider that these 2 cases developed complications due to their medical conditions rather than the use of fondaparinux. We concluded that fondaparinux can be safely used in patients with kidney disease, granted that Factor Xa activity is measured, the risk of bleeding is weighed to the risk of thrombosis and the dose is individualized. However, our sample size is small and further studies with a larger number of patients are needed to draw a conclusion.